2016
DOI: 10.1161/hypertensionaha.116.07572
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein–Coupled Receptor MrgD Is a Receptor for Angiotensin-(1–7) Involving Adenylyl Cyclase, cAMP, and Phosphokinase A

Abstract: Angiotensin (Ang)-(1–7) has cardiovascular protective effects and is the opponent of the often detrimental Ang II within the renin–angiotensin system. Although it is well accepted that the G-protein–coupled receptor Mas is a receptor for the heptapeptide, the lack in knowing initial signaling molecules stimulated by Ang-(1–7) prevented definitive characterization of ligand/receptor pharmacology as well as identification of further hypothesized receptors for the heptapeptide. The study aimed to identify a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 34 publications
3
115
3
Order By: Relevance
“…This notion is further emphasized by the recent discovery of MrgD as another novel receptor for Ang- (1-7) regulating the physiological arterial pressure. 9 Physiological relevance of the Ang-(1-7)/AT1-R axis could be, however, questioned given that the affinity/potency of Ang-(1-7) for AT1-R is modest (≈300 nmol/L) and relatively far from plasma concentrations generally described, with significant differences in between rodents (nmol/L) 26,27 or human species (pM). [28][29][30] Nevertheless, despite the RAAS was originally described as a circulating system, it is now widely accepted that a distinct local RAAS does exist in several tissues, 31 thus promoting a close ligand-receptor proximity to ensure an accurate spatiotemporal regulation of RAAS actions similar to that observed for neurotransmitters concentrations in the synaptic cleft after release.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is further emphasized by the recent discovery of MrgD as another novel receptor for Ang- (1-7) regulating the physiological arterial pressure. 9 Physiological relevance of the Ang-(1-7)/AT1-R axis could be, however, questioned given that the affinity/potency of Ang-(1-7) for AT1-R is modest (≈300 nmol/L) and relatively far from plasma concentrations generally described, with significant differences in between rodents (nmol/L) 26,27 or human species (pM). [28][29][30] Nevertheless, despite the RAAS was originally described as a circulating system, it is now widely accepted that a distinct local RAAS does exist in several tissues, 31 thus promoting a close ligand-receptor proximity to ensure an accurate spatiotemporal regulation of RAAS actions similar to that observed for neurotransmitters concentrations in the synaptic cleft after release.…”
Section: Discussionmentioning
confidence: 99%
“…MrgD leads to an increase in adenylyl cyclase activity, consequently increasing cAMP levels, thereby activating protein kinase A, and leading to cAMP response elementbinding protein phosphorylation. 24 Additionally, it has been shown that alamandine, via the MrgD receptor, can promote the stimulation of eNOS and the subsequent generation of NO, and thereby exerts its vasodilatory and anti-hypertensive actions. 5 The AT2R receptor stimulates various signaling pathways, which can be categorized into 3 broad types: regulation of protein phosphorylation, activation of phospholipases, and regulation of NO/cyclic guanosine monophosphate (cGMP).…”
Section: Discussionmentioning
confidence: 99%
“…These ligands activate the Mrgprs to initiate the signaling cascades coupled to G q/11 and pertussis toxin (PTX)-sensitive G i/o proteins, activation of which mobilizes PTX-insensitsitive intracellular Ca 2+ and PTX-sensitive inhibition of forskolin-induced activation of adenylyl cyclase [43]. There is also evidence that additional receptors, such as AT 2 receptors and MrgD receptors, may be involved in mediating the effects of ANG (1–7) [47,48,171173]. …”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%